Economic report of the President transmitted to the Congress. - United States. President; Council of Economic Advisers (U.S.). (Washington U.S. G.P.O.)
Reports for <1984-> include: The annual report of the Council of Economic Advisers.
G.P.O. sales information incorrect in publication; only dept. ed. for sale.
Description based on: 1981.
Vols. for <1983-> distributed to some depository libraries in microfiche.
Dept. ed. also available from GPO Access via Internet at the GPO Web site.
Keywords: United States. -- Economic policy. -- Periodicals; United States -- Economic conditions -- 1945- -- Periodicals